(untitled) (Latakia University Journal -Biological Sciences Series, 2023)
The study was conducted during the seasons 2021 and 2022 on peach trees, Prunus persica L., cultivar "Red haven", grown in the village of Khirbet Solas in Lattakia Governorate, at an altitude of 500 meters above sea level. The results showed the following: -The treatment with biofertilizer and seaweed extract (EM1 6 cm3/L + Casper Fix 1.5 cm3/L) gave the highest value of increase in tree crown volume in the two seasons, reaching (2.90 m3) for the first season and (3.85 m3) for the second season compared to the control (0.97 m3). and 0.68 m3), respectively. The percentage of increase in the size of the tree crown was (40.41%) for the first season and (45.94%) for the second season, while this increase did not exceed (15.49% and 15.09%) in the witness during the years 2021 and 2022, respectively. The results of the statistical analysis showed its superiority over all other treatments, including the control. - Treatment with (EM1 6 cm3/L + Casper Fix 1.5 cm3/L) gave the highest leaf content of chlorophyll a in the first and second seasons (1.80 mg/g) and (1.81 mg/g) respectively; This treatment also achieved the highest value of leaf content of chlorophyll b during the two seasons (0.79 mg/g and 0.87 mg/g), respectively. The results of the statistical analysis showed that this treatment was superior to all other treatments in terms of the average of the two years (1.80 mg/g). - Foliar feeding with the biofertilizer EM1 and seaweed extract Casper Fix increased the percentage of set flowers, both when single spraying or mixed spraying and in all treatments compared to the untreated control; As this percentage ranged between (43.19% and 46.58%) as an average for the two years, while it did not exceed 32.22% in the control. The results of the statistical analysis showed that all treatments were superior to the control, without a significant difference between them.